Tweeting About a Revolution? A Cross-National Analysis of Tweets on Climate Change During the Rise of “Fridays for Future” - Valentina Rizzoli; Bruno Gabriel Salvador Casara; Mauro Sarrica (Social Psychological Bulletin)
In 2018, thanks to the use of social media, the Fridays for Future (FFF) movement brought global attention to climate change. However, in the post-Covid era, the rhetoric of a return to normality seems to have marginalized those issues from the media debate. Looking at the emergence of FFF, the paper applies topic detection to analyze 19,112 tweets on climate change. The emerging contents of social representations are examined in relation to sociocultural (power distance; individualism; uncertainty avoidance; long-term orientation) and structural (level of pollution) factors associated with the country of origin of the tweets. The primary topic among those identified focuses on calls to action, particularly related to the FFF movement. When this topic is absent, others address efforts to mitigate global warming or strategies for adapting to climate change impacts. The main results indicate that tweets from the most polluted countries and from countries high in short-term orientation are more centered on topics concerning a posteriori response to climate change, also denying it as a defense mechanism. This could prevent imagining alternative futures and the projection of concrete means of countering climate change. The study suggests the importance of transcending the on-line and off-line distinction, not only for mobilization but also to form an arena for debate toward social change.